2010
DOI: 10.4103/0028-3886.68676
|View full text |Cite
|
Sign up to set email alerts
|

Underlying prothrombotic states in pregnancy associated cerebral venous thrombosis

Abstract: In patients with pregnancy associated CVT, prothrombotic markers can be multiple and are associated with increased odds of mortality. Deep venous system involvement, presence of midline shift and diffuse cerebral edema increased mortality. Peuperial water restriction may be a modifiable risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Aaron et al . [19] in their study of 41 patients reported that 34% had hyperhomocysteinemia with a 17% mortality. Similarly in our study, 24% of the population had hyperhomocysteinemia with an overall mortality rate of 16%.…”
Section: Discussionmentioning
confidence: 99%
“…Aaron et al . [19] in their study of 41 patients reported that 34% had hyperhomocysteinemia with a 17% mortality. Similarly in our study, 24% of the population had hyperhomocysteinemia with an overall mortality rate of 16%.…”
Section: Discussionmentioning
confidence: 99%
“…More than 90% of the CVST occurs in people below 60 years of age and it is more commonly seen in women between 20 and 35 years. Young women have a higher risk due to pregnancy, puerperium, and oral contraceptive usage (1620). The incidence of CVST is estimated to be 1–13 cases per 100,000 per year (5, 16, 21).…”
Section: Introductionmentioning
confidence: 99%
“…A study from the same region[ 9 ] had earlier found that a traditional practice of restricting water in the postpartum period can be a modifiable risk factor in postpartum CVT.…”
Section: Discussionmentioning
confidence: 99%